2020
DOI: 10.1186/s12895-020-00116-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients living with psoriasis: a qualitative study

Abstract: Background Psoriasis is a multifactorial inflammatory disease prevalent in dermatology. We aimed to understand the perceptions of patients living with psoriasis in relation to their quality of life and to identify aspects to improve it. Methods This is qualitative research carried out in a dermatology outpatient clinic of the São Paulo State University (UNESP) medical school, Botucatu, Brazil, with 81 psoriasis patients. The interviews were transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 20 publications
0
19
0
5
Order By: Relevance
“…The social and psychological impact of psoriasis is generally underestimated by healthcare professionals [ 25 , 26 , 27 ] and endpoints used in clinical studies do not capture the full impact of this condition [ 28 ]. Therefore, the perception of QoL is considered a critical measure in dermatology [ 29 , 30 ] and there is an urgent need to refine QoL measures to identify issues not frequently included in QoL instruments in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The social and psychological impact of psoriasis is generally underestimated by healthcare professionals [ 25 , 26 , 27 ] and endpoints used in clinical studies do not capture the full impact of this condition [ 28 ]. Therefore, the perception of QoL is considered a critical measure in dermatology [ 29 , 30 ] and there is an urgent need to refine QoL measures to identify issues not frequently included in QoL instruments in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that patients with psoriasis report physical discomfort and limitations in their daily activities and social contacts [ 15 , 16 ]. They also experience severe itching and pain, as well as plaques coming loose and falling from their skin [ 17 ]. These symptoms can cause significant distress and feelings of embarrassment and shame, with significant impacts on functioning across social and employment domains [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also experience severe itching and pain, as well as plaques coming loose and falling from their skin [ 17 ]. These symptoms can cause significant distress and feelings of embarrassment and shame, with significant impacts on functioning across social and employment domains [ 17 ]. The visible nature of psoriasis can cause stigma, lowered self-image, depression, anxiety, and suicidal ideation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Psoriasis impacts the physical, emotional and social well-being of patients thereby diminishing their quality of life. 6 Several tools are available to measure and quantify psoriasis. Psoriasis Area and Severity Index (PASI) score is most thoroughly validated for the assessment of clinical severity of psoriasis.…”
Section: Introductionmentioning
confidence: 99%